Islam and the Provisions of War - Iwansyah, Henry (Universitas Islam Negeri Raden Intan Lampung, 2018)
This article compares the provisions of war in Islam with the provisions contained in International Humanitarian Law (The four Geneva Conventions of 1949 and their Additional Protocols). The aim is not to judge Islamic according to or vice versa, but rather, to discover similarities and differences between the two regulations in governing the conduct of war. The study uses a comparative approach, exploring the Islamic values of ethics and rules of conduct of war and then comparing them with similar provisions of international humanitarian law. This article also analyzes the possibility of synthesizing the two legal system. Having reviewed the topic thoroughly, this study concludes that, in principle, there is no difference between Islamic law and international humanitarian law in regulating procedures and ethics of warfare. Both of the legal system are equallyconcern to regulate the behaviour of warriors by limiting the use of force and minimizing the impact of the battles to civilians